Healthcare Providers’ Perspectives and Role in Improving Patient Engagement in HIV Treatment and Care in Almaty, Kazakhstan - Elizabeth J. King (MDPI AG, 2021)
The HIV epidemic continues to grow in Eastern Europe and Central Asia. At the same time, there are major gaps in engagement in HIV treatment and care among people living with HIV (PLHIV) in the region, including Kazakhstan. Healthcare providers may have the potential to improve patients’ initiation of and adherence to HIV treatment; however, their perspectives and experiences are often overlooked in the research from Kazakhstan. The purpose of our study was to gain an in-depth understanding of how providers perceive the factors influencing PLHIV’s engagement in HIV treatment and care and to identify opportunities for expanding the role that providers can have in improving patient initiation and adherence to treatment in Kazakhstan. Through purposive sampling, we conducted in-depth interviews with 14 healthcare providers at the City AIDS Center in Almaty. We used team-based coding and thematic analysis in order to analyze the data. Quotes from providers were translated from Kazakh and Russian to English to illustrate the themes. Our results show that providers currently view their role as the need to break down myths around ART medications, and to educate and motivate patients to accept their diagnosis and learn to live with HIV. The need to address stigma and social isolation among PLHIV, the risk of overworked providers, and the need to improve patient-provider communication strategies are areas to consider for further interventions. Patient-provider communication interventions are needed in Kazakhstan in order to help meet the country’s 90-90-90 HIV targets.